Mindfulness As Metacognitive Practice - Kudesia, Ravi S. (Academy of Management Review, 2019)
The dangers of mindless behaviors remain better defined than their remedies. Even as mindfulness becomes increasingly prevalent, we lack clarity on three key questions: What is mindfulness? How does mindfulness training operate? And why might mindfulness matter for organizations? In this article I introduce a new conceptualization of mindfulness, which I call metacognitive practice. Metacognitive practice is so named because it blends insights from metacognition and practice theory to answer these three key questions. First, when seen as metacognitive practice, mindfulness is not a single mode of information processing to be applied in all situations. Instead, it is a metacognitive process by which people adjust their mode of information processing to their current situation. Second, this metacognitive process is made possible by three specific beliefs that supersede lay beliefs about human information processing. A core function of mindfulness training, thus, is to provide a context that cultivates these beliefs. Third, when these beliefs are put into practice, people gain greater agency in how they respond to situations. This matters for organizations, because as people interrelate their individual actions into a collective response, metacognitive practice can get embedded in amplifying processes that transform the organization—or in fragmentation processes that threaten it.